Engineering properties of Nanosilica modified asphalt binder/ Ahmad Kamil Arshad...[et al.] - Arshad, Ahmad Kamil; Samsudin, Mohamad Saifullah; Masri, Khairil Azman (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
The effect of nanosilica (NS) on aging resistance as well as stiffness of asphalt binder was investigated. X-ray diffraction (XRD) was used to evaluate nanosilica dispersion in asphalt binder. Nanosilica modified binder (NSMB) samples were aged using the rolling thin film oven (RTFO) and pressure aging vessel (PAV) to simulate short-term and long-term aging processes of asphalt binder before testing. The fourier transform infrared spectroscopy (FTIR) and dynamic shear rheometer (DSR) were carried out to obtain the chemical and rheological properties of NSMB. From the XRD test, it was found that the addition of NS changed the phase of the base asphalt binder from amorphous to semi-crystalline. FTIR spectroscopy showed that the addition of NS into the asphalt binder can delay and weaken the oxidation reaction binder which could improve the aging resistance. From DSR test, it was found that the addition of NS significantly increased the G*/sin δ value and decreased the strain value of asphalt binder. This showed that the addition of nanosilica in asphalt binder results in higher elasticity and is beneficial in increasing the rutting resistance compared to the base asphalt binder.